Internal Drive and External Support: Shaping High Schoolers' Entrepreneurial Intentions. - Mettan, Santho Vlennery; Sancoko, Aldo Hardi (Global Economic, Social, and Development Review, 2025)
Indonesia's population, estimated at 282 million in 2024, presents significant entrepreneurial potential, yet the nation faces a high unemployment rate (8.5%) among high school graduates. To address this, the government launched the National Entrepreneurship Movement (GKN) and incorporated entrepreneurship education into the 2013 Curriculum. Beyond policy, parental influence, student self-belief (Locus of Control), and drive (Need for Achievement) are crucial psychological factors. This study uniquely integrates internal factors (Locus of Control, Need for Achievement) and external influences (Role of School, Role of Parents) to explain high school students’ entrepreneurial intentions in Indonesia a combination rarely examined empirically. The novelty lies in this unified model of psychological and contextual motivators. Using a quantitative survey with 103 respondents selected through purposive sampling, data were analyzed using multiple linear regression (IBM SPSS 26). The findings reveal that Locus of Control, Role of School, and Role of Parents significantly and positively influence entrepreneurial intention; Need for Achievement does not. This study contributes to the Theory of Planned Behavior (TPB) by emphasizing both contextual and psychological antecedents. Practically, the results provide strategic insights for schools and families to enhance Indonesia’s youth entrepreneurship ecosystem and long-term economic resilience.